Geographical variations in the external body proportions of Baird’s beaked whales (Berardius bairdii) off Japan - Kishiro, Toshiya (J. Cetacean Res. Manage., 2023)
The use of morphometrics in stock identification studies for cetaceans has been widely employed. In this study, 14 measurements of external body proportions of 172 Baird’s beaked whales caught by small-type whaling operations off the Pacific coast of Japan, the Sea of Japan and the Sea of Okhotsk from 1988 to 2004 were examined using canonical discriminant analysis (CANDISC) and ANCOVA with body length as a covariate. The canonical variates obtained from the CANDISC could discriminate between whales from the Pacific coast and the Sea of Japan for both males and females, although some overlap was observed. The flipper size (maximum width and straight length) of the Pacific coast whales was significantly larger (3.9-8.3%) than that of the Sea of Japan whales. The canonical variates of the Sea of Okhotsk whales were located in the middle area between the Pacific coast and the Sea of Japan and a significant difference was not observed, however the Sea of Okhotsk samples consisted of data measured by several researchers and so a sampling error may have been introduced. The morphological differences observed between the Pacific coast and the Sea of Japan whales suggest different stocks occur in these two waters.